Mitochondria as pharmacological targets - Moncada, S (Blackwell Publishing Ltd, 2010)
In the last decade, mitochondria have provided a vast area of research for the pharmacologist, with a wealth of potential targets for drug action. Correct target identification and subsequent pharmacological manipulation might greatly help in the prevention and/or treatment of a number of the most prevalent diseases of our time including cancer, neurodegenerative disease and myocardial infarction. This is a commentary to accompany the publication of three papers in this issue of the BJP by Kurz et al., Pravdic et al. and Puerta et al. on different aspects of pharmacology involving mitochondria. This article is a commentary on Pravdic et al., pp. 220–232, Puerta et al., pp. 233–245 and Kurz et al. pp. 246–257 of this issue. To view these papers visit http://dx.doi.org/10.1111/j.1476-5381.2010.00698.xhttp://dx.doi.org/10.1111/j.1476-5381.2010.00663.x and http://dx.doi.org/10.1111/j.1476-5381.2010.00656.x